Responsibilities of the Notary for the Deed of Will that He Makes Violates the Absolute Rights of the Heirs (Legitieme Portie) - Lorensa, Yonatan Dea (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The testamentary grant is a grant regarding goods whose ownership rights only pass to the grantee after the grantor dies. So that if you pay attention to the provisions in Article 875 BW, then the testamentary grant must be made by or before a Notary. then the problem that arises is how the legal consequences of the grant deed that violates the absolute rights of the heirs (Legitieme Portie) and how the Notary's responsibility for the testamentary grant deed that violates the absolute rights of the heirs (Legitieme Portie). Research Method The research method used in this writing is normative juridical by examining library materials or secondary data. The results of this research show that in written law, referring to the explanation and provisions in 1320, the deed of testamentary grant that violates the legitieme portie is considered null and void by itself and is considered to have no binding force from the beginning. Then the liability of Notary includes civil, criminal, administrative responsibilities based on the Notary Office Law, and the Notary Code of Ethics.